(untitled) (Gestão & Regionalidade, 2017)
The goal of this study is to measure the levels of Burnout faced by the internal auditors in their work environment. This is a descriptive study, conducted through a survey on a sample of 124 professionals of the internal audit area in Brazil. Maslach Burnout Inventory - General Survey (MBI-GS) was the instrument used for data collection, aiming at estimating the levels of incidence of Burnout symptoms. Descriptive statistics, factor analysis, reliability testing, correlations and t test were used in the data analysis. The research results showed the existence of Burnout levels in the dimensions of emotional exhaustion, depersonalization and low personal fulfillment, in low, moderate and high levels, but with a predominance of low levels. It is concluded that there is need for greater care in situations that lead to emotional exhaustion, which showed more tendency to Burnout, in this study, in the internal auditors’ working environment.